Rice-Fish-Horticulture Farming System in the North-Eastern Region - Satapathy, B S; Singh, T; Pun, K B (Indian Farming, 2015)
The north-eastern region of India comprising of seven states is blessed with natural resources, natural vegetation, water and fertile soils. To meet out their daily needs each farm family has its own farm pond along with rice field and farmers generally practice pond based farming system. These ponds can be best utilized by adoption of integrated farming system based on rice-fish-horticulture system.